Perancangan Mebel Fasilitas Belajar dan Bermain Anak-Anak Pra-Sekolah dengan Metoda Partisipatoris - Dharmawan, Cherry; Andini, Sanisa Dwi (Waca Cipta Ruang, 2024)
Nowadays, many parents give gadgets to their children when their children are fussy or to keep their children calm, yet there are many negative effects of overuse of gadgets which will have a damaging impact on children's social and emotional development. The negative influence of using gadgets on children include children becoming closed personalities, trouble sleeping, a liking to be alone, aggressive behaviors, fading creativity, and the potential for Cyber ​​Bullying. This article describes the process of designing learning and play facilities for pre-school children using participatory methods at the Al Qur'an Kindergarten (TKQ) Ikhlasunniyah, Bandung. Learning and playing facilities include of a study and play table in one facility for pre-school children. The problem of this research is how to design inexpensive facilities for learning and playing. Aside from that, another issue is how these materials must comply with safety and health standards for pre-school children. This study utilizes a participatory, user-centered method (Human-centered design), an aspect of design thinking. Each phase must involve users. The final product of this research is a prototype of a learning and playing table constructed with used materials from interior projects left over at workshops in Bandung, which is a translation of pre-school children's activities and can train pre-school children's fine motor skills. school, according to their needs.